An Explanation for Unintentional Optimism in Analysts' Earnings Forecasts - Sedor, Lisa M. (The Accounting Review, 2002)
Archival studies report that analysts' annual earnings forecasts are optimistic, particularly for firms reporting recent losses. This study addresses whether forecast optimism is an unintentional consequence of analysts' reactions to the structure of information about managers' future plans. I investigate whether analysts who are forecasting earnings use processes consistent with scenario thinking: envisioning a sequence of events in which proposed actions lead to future outcomes. I study professional sell-side analysts in a 2×2 between-subjects experiment with the structure of information (scenario vs. list) and the sign of prior earnings (loss vs. profit) as independent variables. I find that analysts make more optimistic two-year-ahead earnings forecasts when provided information about a manager's future plans framed as scenarios than when provided the same information framed as lists. I also find that scenario-induced optimism is greater for a firm with prior losses than for a firm with prior profits. The results are consistent with scenario thinking causing analysts to issue optimistic forecasts.